2022
DOI: 10.1016/j.isci.2021.103636
|View full text |Cite
|
Sign up to set email alerts
|

Phagosomal chloride dynamics in the alveolar macrophage

Abstract: Summary Acidification in intracellular organelles is tightly linked to the influx of Cl − counteracting proton translocation by the electrogenic V-ATPase. We quantified the dynamics of Cl − transfer accompanying cargo incorporation into single phagosomes in alveolar macrophages (AMs). Phagosomal Cl − concentration and acidification magnitude were followed in real time with maximal acidification achieved at levels of approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Assuming that the Cl − content and volume gain are both wholly due to the phagosomes, we calculated the mean intraphagosomal [Cl − ] to be 157 ± 78 mM ( Fig. 5 C ), which is consistent with other reports in the literature ( Riazanski et al, 2021 ; Tan et al, 2013 ). Importantly, the net Cl − content gain was missing in cells devoid of ClC-7, which nevertheless ingested a comparable number of zymosan particles ( Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Assuming that the Cl − content and volume gain are both wholly due to the phagosomes, we calculated the mean intraphagosomal [Cl − ] to be 157 ± 78 mM ( Fig. 5 C ), which is consistent with other reports in the literature ( Riazanski et al, 2021 ; Tan et al, 2013 ). Importantly, the net Cl − content gain was missing in cells devoid of ClC-7, which nevertheless ingested a comparable number of zymosan particles ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…In lysosomes, putative counterion pathways for the V-ATPase include the parallel influx of Cl − enabled by Cl − channels ( Di et al, 2006 ; Riazanski et al, 2021 ) or Cl − /H + exchangers ( Graves et al, 2008 ; Kornak et al, 2001 ), as well as cation efflux ( Lin et al, 2015 ; Steinberg et al, 2010 ). As in the case of lysosomes, the generation and maintenance of an acidic steady-state pH in mature phagosomes (phagolysosomes) require the ongoing activity of V-ATPases, which similarly requires a counterion conductance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a counterion conductance pathway which neutralises the charge imbalance. The counterion conductance pathway may be satisfied by the influx of cytosolic anions such as Clinto the lysosome [50,51], Cl -/H + exchangers such as ClC-7 [52], or efflux of cations [53,54]. The role of Clin maintaining lysosomal pH by complementing the V-ATPase is controversial [51][52][53], and more recent research has demonstrated that ClC-7 does not contribute to lysosomal pH, but instead, Clis used to activate lumenal hydrolases [55].…”
Section: Discussionmentioning
confidence: 99%